ANALYSIS ON THE STANDARDS OF BRAZILIAN APPLICANTS AVAILABLE IN THE ADOPTION PROCESS (CIPEEX, 2022)
IT WAS UNDERSTOOD THAT THE CRITERIA OF AVAILABLE SUITORS REGISTERED IN THE NATIONAL ADOPTION ANDFOSTERING SYSTEM (SNA) IN BRAZIL HAS A WELL-DEFINED PATTERN. CURRENTLY, STILL ACCORDING TO THESNA (2021), THERE ARE 32.831 CANDIDATES FOR ADOPTION IN BRAZIL AND 4.263 AVAILABLE CHILDREN.SO, IF THERE ARE ALMOST 8 APPLICANTS FOR EVERY 1 CHILD, WHY HAVEN'T THEY ALL BEEN ADOPTED YET?THE GENERAL OBJECTIVE IS TO ANALYZE THE CRITERIA ADOPTED TO CHOOSE THE APPLICANTS REGISTERED INTHE SNA AND THE REASONS FOR THE NON-ADOPTION. TO REACH THE EXPECTED RESULTS, THE FOLLOWINGSPECIFIC OBJECTIVES WERE DEFINED: A) DEFINE THE STANDARDS IMPOSED BY THE APPLICANTS; B) ANALYZETHE PROFILES OF THE AVAILABLE CHILDREN; C) DISCUSS THE NUMERICAL IMBALANCE BETWEEN APPLICANTSAND AVAILABLE CHILDREN. STILL ACCORDING TO THE SNA, AMONG THE 32,831 APPLICANTS FOR ADOPTION,ONLY 4 WANT TO ADOPT TEENAGERS UP TO OR OVER 15 YEARS OLD, WHILE OF THE 4,263 AVAILABLECHILDREN, MORE THAN 1,000 ARE UP TO OR OVER 15 YEARS OLD. THE WAY OUT WOULD BE NOT TO LET THEAPPLICANTS CHOOSE A STANDARD CHILD TO ADOPT, BUT TO LET THE CHILDREN CHOOSE WHICH FAMILY TO STAYWITH, AND THE APPLICANTS WHO HAVE DECIDED TO ADOPT ARE ALREADY AWARE THAT THEY HAVE NOTCHOSEN THE CHILD, NOR HIS OR HER AGE OR COLOR.
Keywords: processo de adoção; adoção; sna